Light carries on - Nadine, Ray (Dark Horse Comics, 2023)
Adding to his growing list of problems, Leon becomes inexplicably linked to the ghost of a queer punk rocker named Cody, and as the two investigate Cody's mysterious death they also explore the complexities of life, death, love, and their shared love of music.